Rsk2 Knockdown in PC12 Cells Results in Sp1 Dependent Increased Expression of the Gria2 Gene, Encoding the AMPA Receptor Subunit GluR2 - Mehmood, Tahir (MDPI, 2013)
The RSK2 protein is a member of the RSK serine-threonine protein kinase family and is encoded by the X-linked rps6ka3 gene in human. Highly heterogeneous loss-of-function mutations affecting this gene are responsible for a severe syndromic form of cognitive impairment, Coffin-Lowry syndrome. RSK2, which is highly conserved in mammals, acts at the distal end of the Ras-ERK signaling pathway and is activated in response to growth factors and neurotransmitters. RSK2 is highly expressed in the hippocampus, and Rsk2-KO mice display spatial learning and memory impairment. We recently showed that ERK1/2 activity is abnormally increased in the hippocampus of Rsk2-KO mice as well as the expression of the AMPA receptor subunit GluR2. The mechanism via which RSK2 deficiency affects the expression of GluR2 in neural cells was unknown. To address this issue we constitutively suppressed the expression of RSK2 in PC12 cells via vector-based shRNA in the present study. We show that Rsk2 silencing leads also to an elevation of ERK1/2 phosphorylation as well as of GluR2 expression and that the increased level of GluR2 expression results from the increased ERK1/2 activity on the transcription factor Sp1. Our results provide evidence that RSK2 modulates ERK1/2 activity on Sp1, which regulates GluR2 expression through transcriptional activation.